Penelusuran Jejak Islam di Belitung - Andhifani, Wahyu Rizky; Ali, Nor Huda (UI Scholars Hub, 2020)
One of the islands in Indonesia which has both tourist and mining interests is Belitung Island. Belitung Island is an island between Kalimantan Island and Bangka Island. The history of Belitung is said to have existed since the time of the Majapahit Kingdom, while in the Islamic Belitung era it had four kingdoms, namely: the Balok Kingdom (the oldest and largest), Belantu Kingdom, Badau Kingdom, and Buding Kingdom. This study aims to reveal the existence of Islam on Belitung Island, and this is because Belitung Island has many Islamic treasures, some of which have not been disclosed. This research uses explorative and expansive methods. Islam entered Belitung around the end of the 16th century. In the 17th century, Islam in Belitung became an institution of political power with the establishment of the four kingdoms. Sources about the arrival of Islam on the island of Belitung have a variety of stories that developed in the community, and each source is supported by the data on the tombstone findings in several places on the island of Belitung. Assumptions about who spread various versions start from Aceh, Minangkabau, Palembang, Islamic Mataram, Majapahit, Cirebon, Banten, Gresik, and Banjar.